Taro Cocoyam (Colocasia esculenta) Meal as Feed Ingredient in Poultry - Abdulrashid, Mohammed; Agwunobi, Leonard Nnabuenyi (Pakistan Journal of Nutrition, 2009)
Ninety six broiler chickens at four weeks of age were randomly allotted in groups of 12 to the eight experimental diets with three replicates in each treatment and four birds per replicate. The dietary treatment contain 0% 25%, 50% and 100% Cocoyam meal. Taro comprised of raw sundried and boiled sundried forms. There was a significant difference (P < 0.05) in feed conversion with a linear decrease in boiled taro cocoyam meal as substitution levels of inclusion increased. Higher amounts of feed intake were achieved at 50% inclusion levels. Body weight gain decreases linearly (P > 0.05) with increase in Cocoyam meal inclusion levels. The cost of daily feed intake differ significantly (P < 0.05) in raw taro cocoyam meal. The levels of some antinutritional factors were also determined in both raw and boiled, sundried taro cocoyam. Boiling reduced (P < 0.05) the amounts of the antinutritional factors in the taro cocoyam meal. It was also observed that birds on 100% raw sundried taro passed more watery dropping than those on boiled. In the CCYM, the value for proventriculus, crop and all other cuts parts are significantly higher (P < 0.05) as compared with the control. The values of live weight, dressed weight and Eviscerated weight for the cocoyam diet is relatively lower than the control, may be due to effects of antinutritional factors present in cocoyam diets. Thus proper processing of cocoyam meal will effectively replace maize at 25% (raw sundried) and 50% (boiled sundried) as a major source of energy in diets of broiler finishers.